How to effectively build the image of an emerging destination. - Skowronek, Ewa; Brzezińska-Wójcik, Teresa; Stasiak, Andrzej (Quaestiones Geographicae, 2023)
Only a few studies have focused on building the image of emerging destinations. The region’s image is influenced by its tourist attractiveness (image-related perception) and the knowledge about its tourist attributes (recognition). To build the image of emerging destinations, the attributes of attractiveness should be identified. In this study, such an attempt was made for Lublin Province. A diagnostic survey and statistical methods were used to assess the perception of its attractiveness and the recognition of the attractiveness attributes by visitors. Lublin Province has no tourism image, and its attractiveness attributes are identified only vaguely. The landscape is the only attribute on which the image of this destination can be built.